STRESS DEGRADATION STUDIES AND DEVELOPMENT OF STABILITY INDICATING ASSAY METHOD FOR SIMULTANEOUS ESTIMATION OF AMBROXOL HYDROCHLORIDE AND SALBUTAMOL SULPHATE IN BULK AND ITS FORMULATION - Gandhi, lokeshchandra R (Asian Journal of Pharmaceutical Research and Development, 2018)
Simple, rapid, precise, and accurate, reversed phase high performance liquid chromatographic method was developed and validated for simultaneous determination of Salbutamol Sulphate (SALB) and Ambroxol Hydrochloride (AMBR). The chromatographic separation was achieved on Grace 4.6 (id) x 250 mm column at detector wavelength of 224 nm, using an mobile phase consisting of phosphate buffer and acetonitrile in a ratio of 50:50 at pH 3.0 with a flow rate 1 ml/min. The retention time for Salbutamol Sulphate (SALB) and Ambroxol Hydrochloride (AMBR) were found to be 3.8 and 6.2 respectively. The method showed adequate precision with a relative standard deviation (RSD) smaller than 3%. The accuracy was analyzed by adding a standard drug and good recovery values were obtained for all drug concentration used. The HPLC method developed in this study showed specificity and selectivity with linearity in the working range and good precision and accuracy, making it very suitable for quantification of Salbutamol Sulphate and Ambroxol Hydrochloride in tablet dosage form. Degradation studies were carried out under conditions of Alkali Degradation, Acid Degradation, dry heat Degradation, Peroxide Degradation, and UV light and the drug substances were degraded in all conditions. Force degradation studies shows all the degradant peak obtained during degradation were well resolved from main peak of the drugs. The analytical procedure is reliable and offers not only advantages in terms of speed but also met the regulatory requirements for specificity, Linearity, LOD, LOQ, Precision, accuracy.